INDO-EUROPEAN MUSICAL IDIOM AND INDO-EUROPEAN ETHNOGENESIS - НАЗАРОВ, Назарій (Київський національний університет імені Тараса Шевченка, 2021)
This article for the first time proposes a methodological bridge between comparative and historical linguistics, classical philology (on the one hand) and ethnomusicology (on the other hand). Thus, it is possible to verify the results obtained independently in various fields of humanities of the 20th century. The present article compares rhythmical patterns of songs with explicit ritual use from different ethnic groups speaking Indo-European languages (Slavic, Baltic, Greek, Albanian, Iranian, and others). In these songs, there are two main types of stable rhythm patterns (0101/0100 and 011/010) which correlate with two main types of Indo-European poetic metrical patterns independently reconstructed by Indo-European linguistics. It suggests that folk songs preserved a range of possible Indo-European rhythmic patterns, even though languages have changed prosodic properties over time. The present study follows the track of previous studies, which showed partial parallels in Baltic, Slavic-Balcan, and Indo-Aryan song patterns, which loans could not explain. Further analysis of rhythmic patterns revealed their connections with prosodic and syntactic properties of Indo-European sentence. Relative rhythmic complexity of possible Indo-European musical idiom may be correlated to the rhythmic complexity of textiles that may be connected to some Indo-European speaking ethnic groups. The parallels outside the Indo-European cultural range show possible Uralic and Caucasian components of Indo-European musical idiom, which may indicate components of ethnogenesis of Indo-European ethnic groups. Thus ethnomusicology may be regarded as an independent source for studying prehistory, along with linguistics, archeology, and genetics. Though proposed in the 20th century by B. Bartok, V. Goshovsky, G. Luko, this program of ethnomusicological research has not yet been implemented.

У теперішній статті здійснено порівняльний аналіз ритмічних патернів пісень із виразними ритуальними функціями із різних етнокультр, що послуговуються індоєвропейськими мовами (слов'янських, балтських, грецької, албанської, іранських та інших). У цих піснях є дві головні стабільні ритмічні послідовності, що збереглися здебільшого в клаузулах (0101/0100 та 011/010). Ці клаузули корелюють із двома головними типами індоєвропейських метричних зразків, що були незалежно від фольклорних свідчень реконструйовані лінгвістами- індоєвропеїстами в 20 столітті. Це означає, що фольклорні пісні зберегли низку імовірно ще індоєвропейських ритмічних зразків, навіть попри, що з часом мови зазнали просодичних змін. Теперішнє дослідження продовжує часткові спостереження попередніх досліджень, які вказували на часткові паралелі між балтійськими, слов’янськими та індоарійськими пісенними патернами, які не можуть бути пояснені запозиченнями. Глибший аналіз ритмічних патернів показав, що вони пов'язані з просодичними та синтаксичними властивостями індоєвропейського простого речення. Відносна ритмічна складність індоєвропейського музичного ідіому може бути корелятом до ритмічно складної організації візерунків на текстилі із культур, що асоціюютсья з індоєвропейцями. Ритмічні паралелі з-поза індоєвропейського культурного ареалу вказують на можливі уральські та кавказоїдні компоненти індоєвропейського етномузичного ідіому, що може у свою чергу вказувати на компоненти етногенезу давніх індоєвропейців. Таким чином етномузикологія, збагачена лінгвістичним матеріалом, може слугувати незалежним джерелом інформації про доісторію, поряд із лінгвістикою, археологією та генетикою. Саме такою була донині не реалізована програма етномузикологічних досліджень, запропонована в 20 столітті Б. Бартоком, В. Гошовським, Ґ. Люко.
ІНДОЄВРОПЕЙСЬКИЙ МУЗИЧНИЙ ІДІОМ ТА ЕТНОГЕНЕЗ ІНДОЄВРОПЕЙЦІВ
Keywords: індоєвропейці; етномузикологія; фольклор; ритм; Indo-European; ethnomusicology; folklore; rhythm